2013
DOI: 10.1007/s00430-013-0306-1
|View full text |Cite
|
Sign up to set email alerts
|

Detection of herpesvirus EBV DNA in the lower respiratory tract of ICU patients: a marker of infection of the lower respiratory tract?

Abstract: Epstein-Barr virus (EBV) is a lymphotropic herpesvirus causing clinically self-limiting but lifelong persisting infections. Although several severe diseases (e.g., Hodgkin's disease) are associated with EBV, its role in lower respiratory tract infections is still elusive. The prevalence of EBV, herpes simplex virus (HSV) and cytomegalovirus (CMV) in bronchoalveolar fluid (BAL) samples was evaluated in a retrospective study. BAL samples from 135 patients in the intensive or coronary care unit (ICU/ICC) at Unive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 24 publications
1
27
0
Order By: Relevance
“…Similarly, cytomegalovirus (CMV) reactivation can be detected in respiratory secretions of about 16% immunocompetent ICU patients [9]. Much like in HSV, the clinical consequences remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, cytomegalovirus (CMV) reactivation can be detected in respiratory secretions of about 16% immunocompetent ICU patients [9]. Much like in HSV, the clinical consequences remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Several works have reported the detection of EBV DNA in the lower respiratory tract or in the blood of intensive care unit (ICU) patients without showing specific pathogenesis except inflammation. [10,11] During reactivation, EBV produces an interleukin-10 (IL-10) homolog, which is able to disturb the immune response, particularly, the activity of natural killer (NK) and CD4+ T cells. [12] EBV also produces proteins that impair the production of cytokines such as interferon, mainly during the lytic phase.…”
mentioning
confidence: 99%
“…Most of the time, infection is asymptomatic, and is rarely complicated by organ dysfunction. Several studies have reported detection of EBV DNA in the LRT or blood of ICU patients without showing specific pathogenesis, except inflammation . While some studies have involved EBV positivity in LRT or serum samples in specific populations, the potential pathogenicity is still a matter of debate.…”
Section: Discussionmentioning
confidence: 99%
“…EBV infection may induce immune suppression in several ways, which may influence the proper host response to other pathogens and may lead to a bad outcome for critically ill patients. Detection of EBV in lower respiratory tract (LRT) and serum samples have been reported in the ICU population , but the prognostic value of EBV positivity in these samples from critically ill patients with respiratory failure is unclear .…”
Section: Introductionmentioning
confidence: 99%